Associations of caesarean section with body mass and waist circumference trajectories from age 2 to 13 years: A nationally representative birth cohort study in Australia. Issue 7 (5th January 2021) - Begum, Tahmina; Fatima, Yaqoot; Perales, Francisco; Anuradha, Satyamurthy; Mamun, Abdullah
Summary: Background: Measuring obesity at a single time point does not explain the independent association between C‐section birth and obesity in a child's life course. Objectives: This study aimed to explore the longitudinal link between C‐section with obesity trajectories during childhood. Methods: We analysed data from a nationally representative birth cohort study named "Longitudinal Study of Australian Children (LSAC)", commenced in 2004. General obesity was measured through the Body Mass Index (BMI) and abdominal obesity by the Waist Circumference (WC) using the biennially collected data from age 2 to 13 years (2006‐2016). Group‐based trajectory modelling was applied to identify the distinct pattern of BMI & WC trajectories. Multivariable multinomial logistic regression models were used to assess the association between C‐section and obesity trajectories after adjusting for perinatal factors. Results: Of the 3524 study children, 30% were born by C‐section. Three distinct BMI trajectory groups emerged: stable normal (60%), moderately rising (33%) and accelerated (7%). The WC trajectories were, stable normal (58%), moderate (34%) and accelerated (8%). Compared with the stable normal group, children born through C‐section had a higher risk to follow accelerated trajectories for both BMI (OR:1.72; 95% CI: 1.28‐2.32) and WC (OR: 1.51; 95% CI: 1.15‐1.98) with P‐value <0.01. Adjustment of potential confounders did not alter these associations substantially. Conclusions: C‐section birth significantly increases the risk of having an accelerated obesity trajectory in children. Limiting the C‐section for absolute clinical causes and early institution of preventive approach can reduce the obesity burden among children delivered through C‐section.